1980
DOI: 10.1097/00132586-198006000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fentanyl Concentrations and Clinical Observations during and after Operation

Abstract: Thirty patients undergoing major abdominal gynaecological surgery were anaesthetized with a standard technique including nitrous oxide in oxygen and myoneural blockade. The lungs were ventilated with large tidal volumes (10 ml kg" 1 ) but i-'aco, remained within normal limits. Fentanyl was given as a loading dose of 10 | xg kg" 1 or 25 (xg kg" 1 i.v. at the start of the anaesthetic. The lower dose was followed by either an infusion of fentanyl 2 ng min" 1 or by fentanyl given as increments of 100 (ig after 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Secondary peaks in the drug concentration profile occurring at the time of awakening have been observed previously for propofol [ 22, 23] and for other lipophilic intravenous anaesthetic agents such as fentanyl [ 30]. Since the majority of propofol eliminated from the blood during the first 2 h is accounted for by the uptake into peripheral compartments (62%) and not by metabolism [ 31] we hypothesized that alterations in cardiac output at awakening may have led to the release of propofol from lipid tissues [ 32].…”
Section: Discussionmentioning
confidence: 76%
“…Secondary peaks in the drug concentration profile occurring at the time of awakening have been observed previously for propofol [ 22, 23] and for other lipophilic intravenous anaesthetic agents such as fentanyl [ 30]. Since the majority of propofol eliminated from the blood during the first 2 h is accounted for by the uptake into peripheral compartments (62%) and not by metabolism [ 31] we hypothesized that alterations in cardiac output at awakening may have led to the release of propofol from lipid tissues [ 32].…”
Section: Discussionmentioning
confidence: 76%
“…In a previous study (Fujinaga, Stevenson and Mazze, 1986), we administered fentanyl either 10 or 100 ug kg" 1 / day to Sprague-Dawley rats throughout pregnancy or 500 ug kg~yday on days 3-17 of pregnancy using chronically implanted, subcutaneous, osmotic minipumps. The 500-ug kg'yday dose was associated with plasma fentanyl concentrations of 8.5 ng ml" 1 (clinical therapeutic range: 0.5-2.5 ng ml" 1 in general surgery (McQuay et al, 1979); 5-10 ng ml" 1 in cardiac surgery (Bovill and Sebel, 1980)) and was the largest dose we could administer with osmotic minipumps without producing respiratory depression. In our study, no adverse reproductive effects were observed with any dose of fentanyl.…”
Section: Discussionmentioning
confidence: 95%
“…Fentanyl is a potent, short-act ing narcotic which is frequently used in the practice of neurosurgical anesthesia. Like all narcotics, its use may precipitate respiratory de pression and/or nausea [1,3]. Chest wall rigidity has also been re ported with fentanyl use [4].…”
Section: Discussionmentioning
confidence: 99%